2020
DOI: 10.1186/s13075-020-02292-y
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian dysfunction with moderate-dose intravenous cyclophosphamide (modified NIH regimen) and mycophenolate mofetil in young adults with severe lupus: a prospective cohort study

Abstract: Background Ovarian toxicity is a dreaded complication of cyclophosphamide (CYC). With the use of lower cumulative doses of intravenous CYC (modified NIH regimens) and availability of better markers of ovarian toxicity, the incidence of ovarian dysfunction needs reassessment. Lupus disease activity, by itself, is also believed to affect ovarian function negatively. Methods This single-centre prospective cohort study recruited 50 female patients of severe lupus aged 18–40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…31,32 The mechanisms of CYC to induce anxiety are explained by E2 withdrawal due to ovarian injury and increased oxidative stress. 12,33 In our study, the dose of CYC determined to create a POF model caused damage to the ovaries, created anxiety-like behaviors, and decreased serum E2 levels, but this decrease was not significant. 12,17 This shows that E2 withdrawal time is not sufficient.…”
Section: Discussionmentioning
confidence: 61%
“…31,32 The mechanisms of CYC to induce anxiety are explained by E2 withdrawal due to ovarian injury and increased oxidative stress. 12,33 In our study, the dose of CYC determined to create a POF model caused damage to the ovaries, created anxiety-like behaviors, and decreased serum E2 levels, but this decrease was not significant. 12,17 This shows that E2 withdrawal time is not sufficient.…”
Section: Discussionmentioning
confidence: 61%
“…Indeed, cyclophosphamide, which is used as a first-line immunosuppressive medicine in the treatment of life-threatening organ involvement of SLE, SSc and vasculitides, is an alkylating agent that causes gonodotoxicity. Consistent with this general knowledge, recent studies showed an increased risk of ovarian failure in SLE patients treated with cyclophosphamide compared to SLE patients treated with mycophenolate, azathioprine, calcineurin inhibitors, and steroids [18][19][20]. For RA patients, there are inconsistent studies.…”
Section: Premature Ovarian Insufficiency In Autoimmune Diseasesmentioning
confidence: 80%
“…In another study, it has been reported about the ameliorative effects of CoQ10 on Follicle Stimulating Hormone Receptor and Proliferating Cell Nuclear Antigen genes, IVF rate, and embryo development in cyclophosphamide‐induced mice model of ovarian injury (Delkhosh et al, 2019). On the other hand, a moderate intravenous dose of cyclophosphamide along with mycophenolate mofetil treatment has been found to be effective in severe systemic lupus erythematosus young adults accompanied with mild or negligible gonadotoxicity (Sharma et al., 2020). Similarly, isoliquiritigenin and formononetin derived from G. glabra have been reported to improve the IVF rate in mice (Tung et al., 2015).…”
Section: Discussionmentioning
confidence: 99%